Analisis Penerapan Sistem Informasi Manajemen SMART Pada Kegiatan Purcashing Request di PT XYZ - Dewi Untari; Endang Pudji Widjajati (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
To maintain the smooth operation of the company, efficient inventory management becomes a crucial aspect. Essential regulation involves managing the inflow and outflow pf goods. With the company’s growth, the task of managing available inventory becomes increasingly complex and high-risk. PT XYZ is one of the service-oriented industries, particularly in hospitality service. This research aims to assess the extent of efficiency in implementing softwere-based Management Information Systems (SMART) in the purchasing request or procurement of operational necessities within the hotel industry. The research methodology employed a qualitative descriptive approach, gathering data through observations, interviews, and documentation. The research findings delineated an overview of PT XYZ’s back office management information system, analyze the advantages of applying this system, identify operational challenges, as well as management hurdles and influential factors affecting the operation the back office infotmation system.